Helping developers help themselves: Automatic decomposition of code review changesets - Barnett, Mike; Bird, Christian; Lahiri, Shuvendu; Brunet, Joao (Proceedings of the 37th International Conference on Software Engineering, 2015)
Code Reviews, an important and popular mechanism for quality assurance, are often performed on a changeset, a set of modified files that are meant to be committed to a source repository as an atomic action. Understanding a code review is more difficult when the changeset consists of multiple, independent, code differences. We introduce CLUSTERCHANGES, an automatic technique for decomposing changesets and evaluate its effectiveness through both a quantitative analysis and a qualitative user study.